PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL QUANTUM LEARNING DI KELAS VI SD - Sari, Erna; Mayarnimar, Mayarnimar; Taufina, Taufina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe the improvement narrative writing skills using a Quantum Learning models in grade V student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SD Negeri35 Parak Karakah, Padang city with a total of 21 students consisting of 12 female students and  9 male students.  Value of narrative writing skills at the pre-writing stage at cycle I 55,35 (K) increases on cycle II 94,04 (SB). The writing phase in the first cycle 42,8 (K), increased in the second cycle 78,27 (B), the post-writing phase cycle I 46,42 (C) increases in cycle II  90,77  (SB).  Keywords: Improvement narrative writing skills using a Quantum Learning models.